2022
DOI: 10.1038/s41418-022-01012-0
|View full text |Cite
|
Sign up to set email alerts
|

Loss of RBMS1 promotes anti-tumor immunity through enabling PD-L1 checkpoint blockade in triple-negative breast cancer

Abstract: Immunotherapy has been widely utilized in multiple tumors, however, its efficacy in the treatment of triple-negative breast cancers (TNBC) is still being challenged. Meanwhile, functions and mechanisms of RNA binding proteins in regulating immunotherapy for TNBC remain largely elusive. Here we reported that the RNA binding protein RBMS1 is prevalent among immune-cold TNBC. Through a systematic shRNA-mediated screen, we found depletion of RBMS1 significantly reduced the level of programmed death ligand 1 (PD-L1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…The activation programmed cell death (PD)-1 pathway, which mediates cancer immune evasion, has become an attractive therapeutic target in TNBC [41]. Several studies have shown that the expression level of PD-L1 in TNBC cells correlates with immunotherapy response and overall prognosis [41][42][43]. Interestingly, our RNA sequencing data showed that RNF31 could be a possible inhibition factor for PD-L1 in TNBC.…”
Section: Discussionmentioning
confidence: 81%
“…The activation programmed cell death (PD)-1 pathway, which mediates cancer immune evasion, has become an attractive therapeutic target in TNBC [41]. Several studies have shown that the expression level of PD-L1 in TNBC cells correlates with immunotherapy response and overall prognosis [41][42][43]. Interestingly, our RNA sequencing data showed that RNF31 could be a possible inhibition factor for PD-L1 in TNBC.…”
Section: Discussionmentioning
confidence: 81%
“…The latest study report shows that B4GALT1 is a newly discovered PD-L1 glycosyltransferase, and in triple-negative breast cancer, RBMS1 can bind to the 3′-UTR of B4GALT1 to stabilize its mRNA. Subsequently, highly expressed B4GALT1 can promote PD-L1 glycosylation and increase PD-L1 protein stability, weakening the body's antitumor immune response and promoting tumor immune escape (Zhang et al, 2022). Frontiers in Genetics frontiersin.org However, in LAML, the relationship between B4GALT1 and immune infiltration has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…B4GALT1 expression was positively correlated with PD-L1 and CTLA4 expression in bladder cancer ( 93 ). In TNBC, RNA binding motif single strand interacting protein 1 (RBMS1) positively regulates B4GALT1 expression, which is related to the inhibition of inflammation and PD-L1-mediated antitumor immunity ( 94 ). Mechanistically, RBMS1 increases the stability of B4GALT1 mRNA and promotes B4GALT1-mediated PD-L1 galactosylation in N-glycans, thereby reducing PD-L1 protein degradation ( 94 ).…”
Section: Significance Mechanism and Possible Use Of Pd-l1 Glycosylati...mentioning
confidence: 99%
“…The glycosylation process mainly involves the sequential action of different glycosyltransferase families, and their expression and function are strictly regulated in each cell ( 100 ). In addition to STT3, B3GNT3, B4GALT1 and α-mannosidase II, which are involved in PD-L1 glycosylation ( 54 , 71 , 94 , 98 ), other glycosyltransferases involved or possibly involved in PD-L1 glycosylation have also been explored. Glycosyltransferase 1 containing domain 1 (GLT1D1) is highly upregulated in incurable B-cell non-Hodgkin’s lymphoma subtypes and early relapsed diffuse large B-cell lymphoma ( 101 ) and may be associated with poor prognosis of colon cancer ( 102 ) and multiple myeloma ( 103 ).…”
Section: Significance Mechanism and Possible Use Of Pd-l1 Glycosylati...mentioning
confidence: 99%